Evolution of clinical guidelines for antimicrobial management of Clostridioides difficile infection. (May 2021) - Chaar, Abdelkader; Feuerstadt, Paul
Clostridioides difficile infection (CDI) has been an epidemic for many years. Our biggest challenge in treating CDI is preventing recurrence, which is seen in approximately 25% of patients with initial infection and in 40–60% of those with subsequent episodes. Given the major disease burden of this infection, appropriate data-driven treatment remains essential. Clinical treatment guidelines provide an unbiased critical analysis of the literature, integrating the quality of the available data to make recommendations. As CDI has been evolving and more research has become available, the frequency of guideline issue from various global societies has increased, as has the detail of the recommendations to fit more relevant clinical scenarios. In this review, we will discuss clinical guideline recommendations over three time periods: The Initial Guidelines 1995–1997, The Second Wave 2009–2013, and The Modern Era 2014–present. We see the changing recommendations from metronidazole or vancomycin for initial infection during earlier times to preferential treatment with fidaxomicin within the Infectious Diseases Society of America (IDSA) and Society of Healthcare Epidemiology of America (SHEA) joint guidelines provisional update in late 2020. The recommended treatments for first recurrence were initially with the same antimicrobial as the first episode but have since changed to having multiple options for one or more recurrences. We have also seen the addition of immune boosting treatments, including fecal microbiota transplantation (FMT)/microbiota restoration therapy (MRT) and bezlotoxumab in the more modern recommendations. As the guidelines are evolving with the times, it remains important to understand the differences among them so we can apply this information clinically and optimize patient outcomes.